Contemporary Muslims and human rights discourse: a critical assessment - Umar Ahmad, Kasule (IIUM Press, 2009)
This book is a majpr departure from what many may regard as the general trend of studies by Muslims on the human rights tradition. Whereas most authors on the subject ardently argue the case for human rights by tracing it from the traditional Islamic religious sources, this study poses an antithesis to that trend. The point of departure in this work is found in its in-depth investigation and critique of the theoretical foundations of the human rights issued by international organizations such as the United Nations or the Organization of African Union (now defunct) or the Cairo Declaration. Instead the real meaning of the human rights values should be found in the philosophical thought of its original authors, the Western thinkers, as well as in their common but unique experience in the historical process vis-a-vis the rest of humanity especially the orient, where the Islamic civilization thrives this day.